Efici??ncia energ??tica em edifica????es - estudo de caso tribunal de justi??a de S??o Paulo - Ferrador Filho, Antonio Luiz (2017)
The building sector is one of the largest consumers of energy in global terms, hence the importance of search for energy efficiency in this Field. According to the buildings life cycle, it is in the operational phase in which the highest energy consumption occurs. This research aimed to identify opportunities for energy efficiency improvements in a public, existing and operational Tribunal de Justi??a de S??o Paulo building. The applied method was the case study. Data were collected in unstructured interviews and technical visits at the site, as well as related documentation examination. The data were analyzed by the PROCEL-Edifica prescriptive method, obtaining energy classification for the three characteristics of the building: the envelope got the label C, the illumination got label C and the conditioning of air got label B. The building general classification obtained was label C. The implications of this work for practice are in indicating potential improvements in the building's facilities to increase energy efficiency and in the analysis of potential and limitations for the study replication in other buildings. Some of the potential improvements identified were: change of fluorescent lamps to LEDs, change in the rooms lighting circuit, use of polarized films in the building???s glass, improvement in the vertical and horizontal shading of tower fa??ades by using elements that reduce the direct incidence of sunlight. A basic investment payback period analysis for some improvements was conducted, as a examples to a action priorities definition. The method used can serve as a basis of a systematic to be replicated in other TJ/SP buildings. This study can contribute to the enhancement of the TJ/SP Sustainable Logistics Plan, in its line of buildings energy efficiency. In general, the prescriptive method accepted by PROCEL-Edifica criteria is indicated for this study???s replication in other buildings of the TJ/SP, due to the agility to change parameters theoretically and obtain results that may guide the introduction of energetic efficiency improvement measures. However, the ???envelope??? dimension evaluation has a more complex replication and possibly will require trained technicians participation when analyzing other buildings.